2022
DOI: 10.1039/d2rp00011c
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of education with the STEM approach in the development of entrepreneurial thinking in chemistry students

Abstract: Entrepreneurship is a teachable issue, and certain educational approaches can affect learners' entrepreneurial performance. The purpose of this study was to investigate the effect of education with science, technology, engineering,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The research also showed that project-based learning in the school is insufficiently represented, which is reflected in the inadequate development of entrepreneurial competencies in students. The representation of both is significantly determined by the pedagogical competencies of teachers because research-oriented teaching requires more thinking and proactivity from students, which is confirmed by the research results from other authors (Akrami, 2022). However, the data obtained in the initial part of this research are worrying, indicating that students do not have many opportunities to research during classes, i.e., that there are no experiments, which could affect their motivation to learn chemistry, its use in life situations and the development of vital entrepreneurial skills.…”
Section: Discussionsupporting
confidence: 80%
“…The research also showed that project-based learning in the school is insufficiently represented, which is reflected in the inadequate development of entrepreneurial competencies in students. The representation of both is significantly determined by the pedagogical competencies of teachers because research-oriented teaching requires more thinking and proactivity from students, which is confirmed by the research results from other authors (Akrami, 2022). However, the data obtained in the initial part of this research are worrying, indicating that students do not have many opportunities to research during classes, i.e., that there are no experiments, which could affect their motivation to learn chemistry, its use in life situations and the development of vital entrepreneurial skills.…”
Section: Discussionsupporting
confidence: 80%
“…Besides, self-efficacy is the initial source of motivation in every action taken, especially in entrepreneurship education. This self-confidence refers to people's ability to organize and carry out actions to achieve predetermined goals [14], [18], [19] Reflecting on learning outcomes in ESE is essential in utilising and applying entrepreneurial knowledge directly in the field [10], [11], [20]. We found that students have excellent entrepreneurial self-efficacy and have produced entrepreneurial products.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from that, business marshalling impacts students' business skills. This stage provides the ability and skills to face business risks and human resource management [13] [10]. Human resource management is a strategic step in continuing business development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In broader sense, this is of great interest to a country's economic development, since by influencing the creation of adequate learning environments that encourage entrepreneurship, we create an army of students ready to start new ventures and transform ideas into businesses. In line with this statement, Akrami (2022) claims that educational institutions can provide a suitable field for developing talents and abilities of learners by choosing the most appropriate approach to teaching.…”
Section: Introductionmentioning
confidence: 89%